Do Key Audit Matters Mediate Earning Management - Jamian Habeahan; Reskino Reskino (Jurnal Indonesia Sosial Sains, 2024)
Earnings management is the management of cash in or income and cash out or expenses so that businesses can generate net income. The purpose of this study was to determine the effect of key audit matters on earnings management mediated by audit quality, financial audit committee effectiveness. This research uses quantitative research methods. The data collection method of this research uses documentation techniques. The population used in this study are all companies listed on the Indonesia Stock Exchange obtained from the official IDX website, namely https://www.idx.co.id and the company's website in 2022, totaling 825 companies. The method used in sampling is purposive sampling method. The data analysis method used is a combination of descriptive analysis and quantitative analysis. The results showed that audit quality, effectiveness, financial audit committee mediate the effect of key audit matters on earnings management.